Outcomes after decompressive surgery for severe cerebral venous sinus thrombosis associated or not associated with vaccine-induced immune thrombosis with thrombocytopenia: a multicenter cohort study: original work - Pelz, Johann Otto Lothar; Kenda, Martin; Alonso, Angelika; Etminan, Nima; Wittstock, Matthias; Niesen, Wolf-Dirk; Lambeck, Johann; Güresir, Erdem; Wach, Johannes; Lampmannn, Tim; Dziewas, Rainer; Wiedmann, Markus; et al. (Neurocritical care, 2024)
Clinical observations indicated that vaccine-induced immune thrombosis with thrombocytopenia (VITT)-associated cerebral venous sinus thrombosis (CVST) often has a space-occupying effect and thus necessitates decompressive surgery (DS). While comparing with non-VITT CVST, this study explored whether VITT-associated CVST exhibits a more fulminant clinical course, different perioperative and intensive care unit management, and worse long-term outcome.